Demographic Correlates of Infant Feeding Practices and Growth Performance in the First Year of Life - Leila M. Shinn; Christy C. Tangney; Caitlyn Busche; Christine M. Sharp; Mary C. Mullen (International Journal of Pediatrics)
The aims of this study are (1) to assess changes in infant WHO growth indicators (weight-for-age, weight-for-length, and head circumference z-scores) from birth to 12 months of age as a function of feeding practices (FP) and (2) to describe the proportion of infants experiencing rapid weight gain (RWG; defined as change in weight-for-age z-score of ≥0.67 between birth and six months) among different FP. The modified Infant Feeding Practices Study II questionnaire was administered to 149 diverse caretakers/mothers of infants who were less than six months of age in a pediatric outpatient clinic. Growth as a function of FP was assessed using repeated measures ANOVA, while logistic regression was used to describe the correlates of RWG. The largest proportion of caretakers was African American (37%), 46% completed college, and 48% were enrolled in the Women, Infants, and Children (WIC) program. Regarding FP, 32% of infants were formula fed, and 18% were breastfed, with the remaining being either mixed fed or complementary fed, with nearly 40% of infants demonstrating RWG. While changes in weight-for-age z-scores differed among FP across time (p<0.05), observed patterns for head-circumference-for-age and weight-for-length z-scores did not. Various demographic correlates (caretaker race-ethnicity, education, and WIC enrollment) were associated with FP. Only the patterns of change in weight-for-age z-scores at 9 and 12 months differed among FP (with breastfeeding being the lowest at both time points). Further study is needed to adequately characterize the correlates of infant growth performance and growth patterns among different FP in such diverse samples. Continued research will allow for the development of an easy-to-use, succinct questionnaire that will allow healthcare providers to individualize feeding recommendations for caretakers of infants.